Creative Industry: Two Cases of Performing Arts Market in Indonesia and South Korea - Juju Masunah (Humaniora, 2017)
This article explores the concepts and practices of performing arts market, one of the fifteen sub-sectors of creative industry in Indonesia. This study discusses two performances namely Indonesia Performing Arts Market (IPAM) 2013 in Indonesia and Performing Arts Market in Seoul (PAMS) 2015, South Korea. The data were collected through participatory observation, interview, literature review, and personal reflections. The data were analyzed by using triangulation, member check, compare and contrast, and interpretation. The findings of this research show that the similarity of the two performing arts markets lies in their concept of globalization in regards to world society. The performing arts markets share two similar targets, festival in the country and tour abroad. The main differences between IPAM and PAMS are the scope of the event and the institution holding the event. IPAM showcased the works of Indonesian performing arts, while PAMS showcased the works of Korean performing arts and the arts from other countries. IPAM 2013 was organized by the central government, while PAMS 2015 was organized by Korean Arts Management Services (KAMS) that was financially supported by the central government of South Korea.